Tumpang Tindih Fungsi Pengawasan Komisi Yudisial dan Mahkamah Agung: Tantangan dalam Mewujudkan Peradilan yang Berintegritas - Cindy Amalia; Kurnia Ayu Agustin; Prastian Nur Huda; Herfita Ayu Nayla; Damar Arrya Akbar A (Indo Publishing, 2025)
The judiciary plays an important role in upholding law and justice in Indonesia. To maintain the integrity of judges, two supervisory bodies were established: the Judicial Commission (KY) and the Supreme Court (MA). However, in practice, there is often an overlap of authority between the two institutions, especially in terms of overseeing the behavior of judges. This research aims to trace the root of the overlapping issues by reviewing the legal basis governing the authority of the Judicial Commission (KY) and the Supreme Court (MA), and its impact on the independence of the judiciary. The method used is normative juridical with a statutory and conceptual approach, as well as examining several Constitutional Court decisions related to this issue. The study results indicate that the overlap in oversight functions is caused by unclear boundaries of authority as stipulated in the law, leading to potential institutional conflict. Going forward, it is necessary to align regulations and improve coordination between the Judicial Commission (KY) and the Supreme Court (MA) so that the oversight function can operate more effectively without disrupting the independence of the judiciary.